Gifts - Bogart, Jo Ellen; Reid, Barbara, 1957- (Toronto : Scholastic, 1994)
A grandmother travels around the world and brings back gifts for her granddaughter.
H
b
b
Keywords: Grandmothers -- Fiction; Voyages and travels -- Fiction; Gifts -- Fiction; Stories in rhyme